FERMENTASI BIJI BUAH NANGKA (Artocarpus heterophyllus Lam.) MENGHASILKAN ETANOL OLEH Saccharomyces cerevisiae DENGAN ANALISA KROMATOGRAFI GAS (GC) - Fitriani, Ana; Kartika, Rudi; Akkas, Erwin (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Research of bioethanol production from jackfruit seeds through fermentation using saccharomyces cerevisiae with the addition of tofu waste as nutrition source of microorganism. the aims of this research to determine the concentration of bioethanol that has been produced with the variation of concentration of tofu waste nutrients and variation of fermentation time. the hydrolysis process through enzymatic uses alfa-amylase on liquefaction process and glucoamylase on saccharification process. the fermentation process used Saccharomyces cerevisiae and tofu waste as a source of nutrition. variation of fermentation time 6, 8 and 10 days and variation of tofu waste nutrients concentration 0,75%; 1,5% and 2,25% (w/v). Ethanol content was obtained by gas chromatography analysis, the result showed the highest concentration of bioethanol obtained at the addition of tofu waste nutrients was 1,5% (w/v) and fermentation time for 10 days with bioethanol concentration obtained at 65,72%.